Joy at work [compact disc, unabridged] : organizing your professional life - Kondo, Marie; Sonenshein, Scott (Hachette Book Group, 2020)
Offering stories, studies, and strategies to help you eliminate clutter, using the world-renowned KonMari Method, and based on cutting-edge research, this book will help you overcome the challenges of workplace mess- make space for work that really matters; and enjoy the productivity, success, and happiness that comes with a tidy desk and mind.